2002
DOI: 10.1055/s-2002-23548
|View full text |Cite
|
Sign up to set email alerts
|

Nitroalkanes and Dimethyl Maleate as Source of 3-Alkyl Succinic Anhydrides and (E)-3-Alkylidene Succinic Anhydrides

Abstract: Nitroalkanes react with dimethyl maleate giving a tandem Michael addition/elimination of nitrous acid. The obtained (E)-2-alkylidene dimethyl succinates are: (i) reduced to the corresponding 2-alkyl dimethyl succinates which after hydrolysis produce 1,4-dicarboxylic acids that are prone to convert into the corresponding 3-alkyl succinic anhydrides or (ii) hydrolysed to (E)-2-alkylidenesuccinic acids that are easily cyclised to (E)-3-alkylidene succinic anhydrides.3-Alkyl-dihydro-furan-2,5-diones (3-alkyl succi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…14,17 The analytical and spectral data obtained for 1a-e were in complete agreement with the reported data. [4][5][6][7][8][9][10][11][12][13][14] The reduction of alkylidenesuccinic acids 1 to alkylsuccinic acids using palladium/charcoal and ring-closure of both the alkyl and alkylidenesuccinic acids to the corresponding alkyl and alkylidenesuccinic anhydrides using acetyl chloride as a dehydrating agent is well established. 14 In summary, we have demonstrated an efficient two-step easy approach to (E)-alkylidenesuccinic acids.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…14,17 The analytical and spectral data obtained for 1a-e were in complete agreement with the reported data. [4][5][6][7][8][9][10][11][12][13][14] The reduction of alkylidenesuccinic acids 1 to alkylsuccinic acids using palladium/charcoal and ring-closure of both the alkyl and alkylidenesuccinic acids to the corresponding alkyl and alkylidenesuccinic anhydrides using acetyl chloride as a dehydrating agent is well established. 14 In summary, we have demonstrated an efficient two-step easy approach to (E)-alkylidenesuccinic acids.…”
supporting
confidence: 88%
“…[2][3][4][5][6][7][8] Several methods have been reported [4][5][6][7][8][9][10][11][12][13] for the preparation of these acids/anhydrides but they do not seem to be of general nature. Very recently Ballini et al have demonstrated 14 an elegant 1,8diazabicyclo [5.4.0]undec-7-ene (DBU)-induced general coupling of nitroalkanes with dimethyl maleate to obtain these acids/anhydrides. Barrett et al have successfully condensed 15 the maleimide-triphenylphosphine adduct with D-ribose to complete the synthesis of showdomycin and epishowdomycin.…”
mentioning
confidence: 99%
“…however, we recorded only a modest 60 % ee for the formation of acid 17. [22] In a search for more efficient conditions we then discovered that a patent [23] reported the preparation of 17 in up to 84 % ee through desymmetrization of the anhydride 11 in the presence of methanol and a catalytic amount of hydroquinidine anthraquinone-1,4-diyl diether [(DHQD) 2 AQN]. Attempts to reproduce these conditions did not at first lead us to record such a high ee, but we became aware that the enantioselectivity of the reaction was highly dependent on the anhydride concentration.…”
Section: Results and Discussion Overall Strategymentioning
confidence: 99%
“…[20] Acidic hydrolysis of 15 [21] afforded the keto-diacid 16, which was next cyclized into the anhydride 11 in acetyl chloride at reflux. [22] By this five-step sequence of reactions, the anhydride 11 could be prepared on a 100 g scale in 66 % overall yield. The anhydride 11 was next subjected to Bolm's conditions as described previously for anhydride 10.…”
mentioning
confidence: 99%
“…The coupling products such as 2‐benzyl succinic acid dimethyl ester are important classes of compounds owing to their utility as intermediates in the synthesis of important targets such as natural antibiotics,5a pyrrolidines,5b metalloproteinase inhibitors,5c inhibitors towards human leukocytes,5d cephalotaxine,5e and monoesters of alkylated succinic acids 5f. Several methods have been reported5b,g,h for this class of compounds, most of which involve multi‐step processes and require the presence of metal catalysts. Alternatively, a photochemical procedure based on electron transfer to a photo‐sensitizer has been proposed for the coupling of methylbenzene and dimethylsuccinate,5i but the method resulted in a complex mixture of reaction products.…”
Section: Data For the Preparative Electrolysis Of Activated Olefins Imentioning
confidence: 99%